Facile Phenylphosphinidene Transfer Reactions from Carbene–Phosphinidene Zinc Complexes. Issue 27 (8th June 2017) - Krachko, Tetiana; Bispinghoff, Mark; Tondreau, Aaron M.; Stein, Daniel; Baker, Matthew; Ehlers, Andreas W.; Slootweg, J. Chris; Grützmacher, Hansjörg
Abstract: Phosphinidenes [R‐P] are convenient P1 building blocks for the synthesis of a plethora of organophosphorus compounds. Thus far, transition‐metal‐complexed phosphinidenes have been used for their singlet ground‐state reactivity to promote selective addition and insertion reactions. One disadvantage of this approach is that after transfer of the P1 moiety to the substrate, a challenging demetallation step is required to provide the free phosphine. We report a simple method that enables the Lewis acid promoted transfer of phenylphosphinidene, [PhP], from NHC=PPh adducts (NHC=N‐heterocyclic carbene) to various substrates to produce directly uncoordinated phosphorus heterocycles that are difficult to obtain otherwise. Abstract : Pass it on : ZnCl2 ‐promoted phosphinidene transfer reactions of the sterically unencumbered carbene–phosphinidene adduct Me NHC=PPh to various substrates (S ) are demonstrated. These unprecedented reactions provided access to new uncomplexed phosphorus heterocycles, which are difficult to obtain otherwise.